The epidemiological impact of HIV antiretroviral therapy on malaria in children. - Greenhalgh, Scott; Ndeffo, Martial; Galvani, Alison P; Parikh, Sunil (AIDS (London, England), 2014)
The objective of this study is to determine the epidemiological effectiveness of a first-line antiretroviral regimen with HIV protease inhibitor for preventing recurrent malaria in children under the range of HIV prevalence levels and malaria transmission intensities encountered in sub-Saharan Africa.